Behavioral presentations of focal onset seizures: A case series - Gaurav Maggu (Wolters Kluwer Medknow Publications, 2021)
Seizures can have varied presentations and may have different etiological factors. A multidisciplinary approach should be used to treat them. It becomes difficult to diagnose seizures if they have an atypical presentation, particularly so when they manifest as behavioral disturbances. This case series demonstrates four cases with different psychiatric and behavioral manifestations of seizures where the diagnosis had to be done in a multi-disciplinary approach. Two of the cases highlight the fact that in the light of normal investigations, paying attention to detailed history is of prime importance.